Comparison of laparoscopic and hand-assisted laparoscopic nephrectomy for inflammatory renal disease: which is the preferred approach?. (January 2021) - Guo, Xudong; Wang, Hanbo; Xiang, Yuzhu; Jin, Xunbo; Jiang, Shaobo
Aims: Management of inflammatory renal disease (IRD) can still be technically challenging for laparoscopic procedures. The aim of the present study was to compare the safety and feasibility of laparoscopic and hand-assisted laparoscopic nephrectomy in patients with IRD. Patients and methods: We retrospectively analyzed the data of 107 patients who underwent laparoscopic nephrectomy (LN) and hand-assisted laparoscopic nephrectomy (HALN) for IRD from January 2008 to March 2020, including pyonephrosis, renal tuberculosis, hydronephrosis, and xanthogranulomatous pyelonephritis. Patient demographics, operative outcomes, and postoperative recovery and complications were compared between the LN and HALN groups. Multivariable logistic regression analysis was conducted to identify the independent predictors of adverse outcomes. Results: Fifty-five subjects in the LN group and 52 subjects in the HALN group were enrolled in this study. In the LN group, laparoscopic nephrectomy was successfully performed in 50 patients (90.9%), while four (7.3%) patients were converted to HALN and one (1.8%) case was converted to open procedure. In HALN group, operations were completed in 51 (98.1%) patients and conversion to open surgery was necessary in one patient (1.9%). The LN group had a shorter median incision length (5 cm versus 7 cm, p  < 0.01) but a longer median operative duration (140 min versus 105 min, p  < 0.01) than the HALN group. There was no significant difference in blood loss, intraoperative complication rate, postoperative complication rate, recovery of bowel function, and hospital stay between the two groups. Multivariable logistic regression revealed that severe perinephric adhesions was an independent predictor of adverse outcomes. Conclusion: Both LN and HALN appear to be safe and feasible for IRD. As a still minimally invasive approach, HALN provided an alternative to IRD or when conversion was needed in LN.